Physical properties of ethylene glycol-based deep eutectic solvents - Ibrahim, Rusul Khaleel; Hayyan, Maan; AlSaadi, Mohammed Abdulhakim; Ibrahim, Shaliza; Hayyan, Adeeb; Hashim, Mohd Ali (Elsevier, 2019)
Deep eutectic solvents (DESs) have been widely recognized as ionic liquids (ILs) analogues due to their low production cost and superior favorable properties over conventional ILs. Studying the physical properties of these solvents will contribute to design processes involving DESs. In this study, five DESs have been successfully prepared using ethylene glycol (EG) as hydrogen bond donor (HBD) with N,N‑diethylethanolammonium chloride (DAC), benzyltriphenylphosphonium chloride (BTPC), choline chloride (ChCl), methyltriphenylphosphonium bromide (MTPB) and tetra‑n‑butylammonium bromide (TBAB) as salts. The freezing point of each of the five studied DESs was measured using Differential Scanning Calorimetry (DSC) and the DES functional groups were identified using the Fourier transform infrared (FTIR) spectroscopy. Moreover, the viscosity, density, electrical conductivity and surface tension were measured at a temperature range of 293.15–353.15 K and they were highly affected by the variation of the temperature. It is worth mentioning that the studied DESs showed many physical characteristics similar to that of ILs, which boost their possibilities to be employed in interdisciplinary domains.